2021
DOI: 10.3171/2019.11.jns192042
|View full text |Cite
|
Sign up to set email alerts
|

Occipital nerve stimulation and deep brain stimulation for refractory cluster headache: a prospective analysis of efficacy over time

Abstract: OBJECTIVEOccipital nerve stimulation (ONS) and deep brain stimulation (DBS) are widely used surgical treatments for chronic refractory cluster headache (CH). However, there is little literature regarding long-term follow-up of these treatments.METHODSThe authors describe two prospective cohorts of patients with refractory CH treated with ONS and DBS and compare preoperative to postoperative status at 6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…The decline in this parameter improved progressively at the 3rd and 6th month and the greatest reductions were registered one year after ONS surgery, of 7.5 attacks per week, which reached 15 at the end of follow-up. The fact that ONS effectivity appears to slightly decrease over time was also reported by Aibar Duran et al [19], but, in their study, the decrease in effectiveness was seen at month 6, and, in our study, it was found later. Despite this fact, our results are hopeful considering that this means a 50% reduction in attacks at the end of follow-up.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The decline in this parameter improved progressively at the 3rd and 6th month and the greatest reductions were registered one year after ONS surgery, of 7.5 attacks per week, which reached 15 at the end of follow-up. The fact that ONS effectivity appears to slightly decrease over time was also reported by Aibar Duran et al [19], but, in their study, the decrease in effectiveness was seen at month 6, and, in our study, it was found later. Despite this fact, our results are hopeful considering that this means a 50% reduction in attacks at the end of follow-up.…”
Section: Discussionsupporting
confidence: 86%
“…Although the ONS is not an economic treatment [25], the direct and indirect cost generated by the usually young patients diagnosed with drCCH widely exceeds the cost of this therapy [26]. Adverse events in our series were much lower than those described in previous cohorts [9,15,17,19,27]. ONS seems to be a safe technique when implants are conducted in highly specialised centers for those CH patients who have failed several preventive treatments, and we think it should be offered as the first option to drCCH patients.…”
Section: Discussionmentioning
confidence: 54%
“…An increased afferent input to the trigeminocervical complex (TCC) with increased peripheral sensitization and a generalized central sensitization of the trigeminospinal or the second order trigeminal neurons can contribute to the development of chronic headache. In addition, a disruption of the descending pain inhibitory pathway can lead to increased sensitization and be relevant in the chronification of headache [1,2,4,17,33,36]. Increased activity in the descending pain pathway in ONS was also shown in a positron emission tomography (PET) study [1].…”
Section: Discussionmentioning
confidence: 97%
“…It is hard to properly assess the incidence of lead migration in ONS since the studies that report it are heterogeneous, describe few cases, and present extremely variable results [ Table 1 ]. [ 2 , 3 , 7 , 11 , 14 , 15 , 17 - 22 , 24 , 28 - 30 , 32 , 34 , 41 ] In our review, we identified five randomized clinical trials which reported lead migration. [ 1 , 8 , 23 , 31 , 33 ] These trials have reported a migration incidence that ranges from 12.9% to 50.9%.…”
Section: Discussionmentioning
confidence: 99%